Clinicopathological, Immunohistochemical, and Genetic Features of Primary Lung Adenocarcinoma Occurring in the Setting of Usual Interstitial Pneumonia Pattern. Issue 12 (December 2016) - Masai, Kyohei; Tsuta, Koji; Motoi, Noriko; Shiraishi, Kouya; Furuta, Koh; Suzuki, Shigeki; Asakura, Keisuke; Nakagawa, Kazuo; Sakurai, Hiroyuki; Watanabe, Shun‐ichi; Hiraoka, Nobuyoshi; Asamura, Hisao
ABSTRACT : Introduction: : An association between usual interstitial pneumonia (UIP) and carcinogenesis has been well established. However, few detailed analyses have investigated the clinicopathological, immunohistochemical, and genetic features of patients with primary lung adenocarcinoma (ADC) with UIP (UIP‐ADC). Methods: : We identified 44 patients with ADC in the setting of UIP (the UIP‐ADC group) (1.9%) from 2309 patients with primary ADC and compared clinicopathological, immunohistochemical, and genetic features between the UIP‐ADC group and patients with ADC without UIP (the non–UIP‐ADC group). Results: : Clinicopathological features of UIP‐ADC included an older age at occurrence; male predominance; smoking history; predilection for the lower lobe; large tumor size; high incidence of lymph vessel invasion, pleural invasion, and lymph node metastasis; and poor survival rate. However, the cause of death of patients with UIP‐ADC was largely influenced by respiratory complications. Histologically, patients in the UIP‐ADC group could be stratified according to invasive mucinous‐predominant subtype. Genetically, patients in the UIP‐ADC group had lower EGFR and higher KRAS mutation rates compared with patients in the non–UIP‐ADC group. Conclusions: : UIP‐ADC was associated with a poor prognosis owing to the high frequency of perioperative complications rather than the malignancy of the tumor itself. There was a high prevalence of the invasive mucinous‐predominant subtype in cases of UIP‐ADC. UIP‐ADC also had a low prevalence of EGFR mutations and a high prevalence of KRAS mutations. These findings suggest that UIP‐ADC should be distinct from non–UIP‐ADC.